Optimalisasi Web E-Commerce Berbasis Prestashop oleh Mahasiswa sebagai Media Penjualan dan Promosi Produk - Mth, Sri Rezky Aprilawati Br; Harahap, Syaiful Zuhri (Journal of Computer Science and Information System(JCoInS), 2023)
The technology that is currently developing is very influential in the sales business process, the offline system is starting to be abandoned and a new system is starting, namely online sales through electronic media. This has an impact on business competition between companies getting higher, therefore one of the product sales efforts which still uses this method is trying to increase sales by implementing a new system, namely online sales through websites. This sales system is a way to increase marketing and sales. In designing this E-commerce website, researchers use the waterfall method which will be applied in the design of e-commerce information systems for businesses. With this media, it is hoped that it can help businesses increase sales with ease of payment with midtrans and be able to make business information systems in business to be better.